PENETAPAN PIDANA MATI DALAM PERPEKTIF HUKUM ISLAM DAN INTERNATIONAL COVENANT ON CIVIL AND POLITICAL RIGHTS (ICCPR) - Rifa'i, Muhammad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
The death penalty is a polemic in the discourse of law and human rights in today's modern world. This is because there is a presumption that the death penalty was considered inhuman punishment. Therefore, the United Nations International Covenant megeluarkan on Civil and Political Rights (ICCPR) as a global treaty that restricts the execution of the country that still has the death penalty. It was considered a solution to keep kelansungan human life includes the right to life, freedom, and human beings have the right to determine his life. View as it affected the Islamic law that still impose the death penalty is deemed to violate human rights. Therefore, the author tries to find common ground between the ICCPR and the fundamental Islamic law. ICCPR and Islamic law possessed the same goal is to maintain public order, protect the whole of society and the state, and yet both of these elements possessed a different approach.